HUBUNGAN STRES KERJA DENGAN PRODUKTIVITAS KERJA KARYAWAN PADA BAGIAN SORTIR DI PT. MARINAL INDOPRIMA - Moh. Maqbul Mawardi (Bayan lin-Naas : Jurnal Dakwah Islam, 2017)
A form of a success company is the optimal of workforce productivity. Therefore, human resources are the one of the important factor for the company in carrying out it is activities to achieve companys’ goals. The increase and decrease of workforce productivity has dealing with job stress. The decrease of workforce productivity is caused by the high of job stress that makes employees feel depressed. Conversely, if job stress is in low level, it will make employees tend to relax in their work and will affect the decline of work productivity. In contrast, when the job stress at moderate level, it is the greatest level of work productivity. This study will examine the strength correlation between job stress and workforce productivity on 60 employees at PT. Marinal Indoprima who have the excessive work duties that must be completed their work in a given amount of time. The method that used in this research is quantitative research with product moment data analysis.The result of this research has significantly negative correlation which obtained = -0.618, that means the higher level of job stress, the lower level of productivity, and vice versa.